Viral Arthtritis in Chicken: Problems and its Control - Dharmayanti, N L P I (Indonesian Animal Sciences Society, 1999)
Viral arthritis in chicken is caused by avian reovirus infection. The infection readily occurs via the egg when the breeder hens go through a viraemia resulting in the virus being transmitted to the progeny. Horizontal transmission occurs through the direct contact. This disease causes leg weakness, swelling the hock joint, lameness, gastrocnemius tendon rupture and femoral head necrosis. Affected birds are reluctant to move, unable to seek food or water and rapidly become dehydrated and die. Economic losses may be due to mortality or culling, reduce growth or egg production on to down to carcass downgrading. Demonstration of Reovirus in the tendon sheath by fluorescent antibody technique (FAT) or isolation in chicken embryo liver (CELi). Group of specific antigens are demonstrable by the agar gel precipitin test (AGPT). Reovirus grows readily in the embryonating chicken egg following inoculation via theÂ yolk sac, chorio allantoic membrane (CAM) or allantoic cavity. Vaccination to induce maternal antibody can be done with inactivated or active vaccines or combinations of both. For prevention of vertical transmission, egg for hatching should be come only from flock known to be free from reovirus infection. Â Key words : Viral arthritis, lameness, vaccination